South American rattlesnake cationic polypeptide crotamine trafficking dynamic in Plasmodium falciparum-infected erythrocytes: Pharmacological inhibitors, parasite cycle and incubation time influences in uptake. (March 2022) - El Chamy Maluf, S.; Hayashi, M.A.F.; Campeiro, J.D.; Oliveira, E.B.; Gazarini, M.L.; Carmona, A.K.
Abstract: Malaria is a parasitic infectious disease caused by Plasmodium sp, which was responsible for about 409 thousand deaths only in 2019. The clinical manifestations in patients with malaria, which may include fever and anemia and that can occasionally lead to the death of the host, are mainly associated to the asexual blood stage of parasite. The discovery of novel compounds active against stages of the intraerythrocytic cell cycle has been the focus of many researches seeking for alternatives to the control of malaria. The antimalarial effect of a native cationic polypeptide from the venom of a South American rattlesnake named crotamine, with ability of targeting and disrupting the acidic compartments of Plasmodium falciparum parasite, was previously described by us. Herein, we extended our previous studies by investigating the internalization and trafficking of crotamine in P. falciparum -infected erythrocytes at different blood-stages of parasites and periods of incubation. In addition, the effects of several pharmacological inhibitors in the uptake of this snake polypeptide with cell-penetrating properties were also assessed, showing that crotamine internalization was dependent on ATP generated via glycolytic pathway. We show here that crotamine uptake is blocked by the glycolysis inhibitor 2-deoxy-D-glucose, and the most efficient internalization is observed at trophozoite stage of parasite after at least 30 min of incubation. The present data provide important insights into biochemical pathway and cellular features determined by the parasite cycle, which may be underlying the internalization and effects of cationic antimalarials as crotamine. Highlights: Crotamine internalization is dependent on glycolysis energy. Crotamine uptake occurs at short period of incubation. Trophozoite stage is more susceptible to crotamine uptake. The data underline the action of cationic antimalarials during the parasite cycle.